PENGALAMAN MENGAJAR CALON GURU PENDIDIKAN ISLAM MELALUI PEER TEACHING DALAM KEGIATAN MICRO TEACHING - Zhul Fahmy Hasani (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
Microteaching is an essential component in developing the pedagogical competence of pre-service teachers, particularly in Islamic Education study programs. One approach commonly applied in microteaching activities is peer teaching, where teaching practice is conducted by students with their peers acting as learners. This article aims to describe the teaching experiences of pre-service Islamic Education teachers through peer teaching in microteaching activities at the Faculty of Tarbiyah and Teacher Training, Universitas Sains Al-Qur’an (UNSIQ). This study employs a descriptive qualitative approach, with data collected through observation, teaching practice reflections, and documentation of microteaching activities. The research subjects were pre-service Islamic Education teachers enrolled in the microteaching course. The findings indicate that the implementation of peer teaching provides students with authentic experiences in lesson planning, developing instructional materials, classroom management, applying teaching methods and media, and conducting learning evaluations. Furthermore, peer teaching enhances students’ self-confidence, communication skills, and ability to give and receive constructive feedback. However, several challenges were identified, including limited teaching practice time, classroom situations that do not fully represent real school conditions, and students’ tendency to be overly tolerant toward their peers. Overall, peer teaching in microteaching activities at the Faculty of Tarbiyah and Teacher Training UNSIQ plays an effective role in preparing professional, reflective, and adaptive pre-service Islamic Education teachers. Therefore, optimizing the implementation of peer teaching is essential as a strategy for strengthening teaching practice in teacher education programs.